Pengaruh Stres Kerja, Dukungan Sosial dan Kepuasan Kerja Terhadap Produktivitas Kerja Generasi Z di Surakarta - Izzuddin Iqbal Kurniawan; Ahmad Mardalis (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study seeks to examine the determinants that trigger or underlie the emergence of work productivity among Generation Z employees in Surakarta by evaluating the roles of job stress, social support, and job satisfaction. The research employs a quantitative approach based on a positivistic paradigm, involving 55 Generation Z employees selected through purposive sampling. Primary data collection was executed via a closed-ended questionnaire using a five-point Likert scale to quantify the variables of job stress, social support, job satisfaction, and work productivity. The instrument’s quality was verified through validity testing, with r-calculated exceeding r-table, and reliability testing using Cronbach’s Alpha with values above 0.60. The data evaluation process in this study implements multiple linear regression techniques, with hypothesis testing conducted through F-tests and t-tests at a 5% significance level. Empirical findings confirm that job stress does not have a meaningful impact on productivity (p = 0.230). Conversely, social support is proven to provide a significant positive contribution (p = 0.036), while job satisfaction emerges as the primary and most potent determinant in driving the productivity of Generation Z employees (p = 0.001). Collectively, this model possesses a predictive power of 59.9%, while the remaining 40.1% of productivity variability is explained by other variables not observed in this research.